Gamma-radiation of heart valves at 4° C; a comparative study using techniques of histochemistry and electron and light microscopy. Issue 1 (January 1973) - Donnelly, R. J.; Aparicio, S. R.; Dexter, F.; Deverall, P. B.; Watson, D. A.
Abstract : The optimal method of valve sterilization and storage is still not known. Pig aortic valve cusps have been studied using techniques of histochemistry, light microscopy, and electron microscopy, and the effects of gamma-radiation at 4° C have been determined. The effects of freezing, β-propriolactone, and freeze-drying were also studied. Gamma-radiation at 4° C and storage at this temperature in a polyionic environment for up to six weeks appears to have minimal adverse effects. This technique of sterilization and storage has now been used in our clinical valve programme for over two years with encouraging results.